2012
DOI: 10.1017/s0021859612000597
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultivar on the changes in protein quality during wilting and ensiling of red clover (Trifolium pratense L.)

Abstract: SUMMARYRed clover (Trifolium pratense L.) silage usually contains lower contents of non-protein nitrogen (NPN) compared with other forage legumes. This is often attributed to the polyphenol oxidase (PPO) activity in red clover, although in most field studies the PPO activity was not measured. Therefore, a laboratory ensiling experiment with three red clover cultivars and one white clover cultivar as control grown in two management systems (with and without mechanical stress) over 2 consecutive years was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(98 reference statements)
1
2
0
Order By: Relevance
“…In all of the mixtures, a higher value of the PA fraction content was achieved compared to the content value of the same in the forages before ensiling (Table 1). This is in accordance with the results of Krawutschke et al (2011), who reported increase of PA fraction in silages of the examined red clover cultivars, when compared with material before ensiling. With an increase in the content of red clover in the mixtures, there is a linear increase in the difference between the value of the PA fraction of the silages and the initial material (Figure 1A).…”
Section: Resultssupporting
confidence: 93%
“…In all of the mixtures, a higher value of the PA fraction content was achieved compared to the content value of the same in the forages before ensiling (Table 1). This is in accordance with the results of Krawutschke et al (2011), who reported increase of PA fraction in silages of the examined red clover cultivars, when compared with material before ensiling. With an increase in the content of red clover in the mixtures, there is a linear increase in the difference between the value of the PA fraction of the silages and the initial material (Figure 1A).…”
Section: Resultssupporting
confidence: 93%
“…If the number of harvests is kept to two or three across the season in the second year after establishment, most modern red clover cultivars would yield comparably well in both the first year and second year after establishment (Wiersma et al 1998). Crude protein levels, and the general quality of the red clover forage, are significantly lower in the second year compared with the first year after establishment (Cassida et al 2000;Krawutschke et al 2012). Even though forage quality diminishes, forage producers would likely maintain red clover in their pastures after the first year because plants still provide reasonable yield, and pasture renovation is costly.…”
Section: Stand Persistencementioning
confidence: 99%
“…In addition, in most forage plants, a large proportion of the N is present as non-protein N (NPN) at harvest (Gierus et al ., 2012; Krawutschke et al ., 2013 a ). After harvesting, NPN is extensively generated by plant-related proteases (Gierus et al ., 2016) or during the fermentation phase of forage conservation (Krawutschke et al ., 2013 b ). After ingestion, high amounts of NPN are counteracted by rapidly fermentable sugars, like water-soluble carbohydrates (WSC), as available energy, resulting in efficient ruminal microbial growth and N utilization (Miller et al ., 1999), contributing to uCP.…”
Section: Introductionmentioning
confidence: 99%